(untitled) (Eurasian Research Bulletin, 2022)
The article provides a brief description of the eco-style used in modern interiors. The main features and materials of eco-style are described. The principle of selection of plants suitable for interior landscaping, as well as the used phytolamps for organizing additional lighting of plants, is presented.